(untitled) - Rogers, Bruce (Boston, 2007)
The Complete Guide to the TOEFL on Computer includes test-taking strategies and extensive practice for all of the new exercise types found on the actual test. -- The book provides a separate section on essay writing, additional exercises addressing the most common errors made on the TOEFL test, and the answer key -- A CD-ROM provides electronic practice through a tutorial, practice with all exercise types found on the TOEFL CBT, one full-length TOEFL test, and a test bank of TOEFL questions
Keywords: English language,English language,Anh ngữ,Anh ngữ; Examinations,Study guides,Bài kiểm tra,Hướng dẫn học